Nanocrystalline MoS2 through directional growth along the (0 0 2) crystal plane under high pressure - Wang, Shanmin; Wang, Zhao; Qin, Jiaqian; Wang, Wendan; Li, Wenyong; He, Duanwei (Materials chemistry and physics, 2011)
The directional growth experiments of graphite-like structured MoS2 crystallites have been conducted by utilizing a designed sample cell assembly under high pressure (2.0 and 5.0GPa) and high temperature (700 degree C). X-ray diffraction (XRD) and scanning electron microscope (SEM) are used to characterize the samples. The results show that the prepared nanocrystalline MoS2 (n-MoS2) crystals have a hexagonal layered structure. The crystal is uncovered to grow preferentially along the (002) plane, which indicates that the low-energy surface is the (002) plane of the crystal. The striking diffuse/broadening nature of Bragg reflection is also analyzed in details, and considered to be associated with the defect structures of the layers stacking and rotational disorder. Measurements of crystallite/grain size are performed by using XRD technique and SEM observation. The measurement results suggest that the traditional peak broadening analysis techniques, including Williamson-Hall formula and Scherrer equation, may not be suitable for the present poorly crystallized n-MoS2 situation. The results may be conducive to have an insight into the growth mechanism and defects analysis of the layer-structured materials.